1983
DOI: 10.1021/ja00361a019
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of ozonation. 1. Electron-deficient alkenes

Abstract: of charge delocalization over charge separation in the annulenones. ConclusionsThe published experimental value for AHfo(g) of diphenylcyclopropenone is too high by as much as 50 kcal/mol corresponding to a 2.5% error in the heat of combustion, possibly due to the presence of a small amount of impurity in the compound tested in the earlier work. More refined calorimetric measure-(28) Greenberg, A.; Liebman, J. F. J . Org. Chem. 1982Chem. ,47, 2084Chem. -2088 ments are in progress. The resonance stabilization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 3 publications
1
35
0
Order By: Relevance
“…Therefore, the formation of the oxidation product 2 is proposed to involve an initial 1,3-dipolar cycloaddition of ozone, an electrophilic specie, towards the C11a-C12 double-bond of 1 to yield an unstable ozonide intermediate [40], which in fact was not detected during the ESI(ϩ)-MS monitoring (Scheme 4). Note that the C11a-C12 double-bond, which is connected to only one electron-withdrawing substituent (the carbonyl group), is proposed to be much more susceptible to the ozone attack than the other available double-bond (C2-C3) of 1, which bears two carbonyl groups [41,42]. The transient ozonide is proposed to quickly decompose, via the release of an O 2 molecule, to generate an unstable epoxide intermediate.…”
Section: Ozonation Of Tetracycline: Mechanism and Product Structuresmentioning
confidence: 99%
“…Therefore, the formation of the oxidation product 2 is proposed to involve an initial 1,3-dipolar cycloaddition of ozone, an electrophilic specie, towards the C11a-C12 double-bond of 1 to yield an unstable ozonide intermediate [40], which in fact was not detected during the ESI(ϩ)-MS monitoring (Scheme 4). Note that the C11a-C12 double-bond, which is connected to only one electron-withdrawing substituent (the carbonyl group), is proposed to be much more susceptible to the ozone attack than the other available double-bond (C2-C3) of 1, which bears two carbonyl groups [41,42]. The transient ozonide is proposed to quickly decompose, via the release of an O 2 molecule, to generate an unstable epoxide intermediate.…”
Section: Ozonation Of Tetracycline: Mechanism and Product Structuresmentioning
confidence: 99%
“…Treatment of this aldehyde with Ph 3 P and CBr 4 then afforded 1,1-dibromoolefin 19 in 94% yield (32). Selective ozonolysis of the primary olefin (33) and Wittig olefination of the resulting aldehyde with Ph 3 PACHCO 2 Me generated the unsaturated ester with the required (E)-configuration in 82% yield and with Ն95:5 selectivity. Reduction of the ester with diisobutylaluminum hydride and oxidation of the allylic alcohol with SO 3 ⅐pyridine then provided aldehyde 14 (34).…”
Section: Chemistrymentioning
confidence: 99%
“…These authors reported that 75% of the oxidation of aromatic hydrocarbons occurs by 1,3 dipolar cycloaddition in the double bond with greatest electronic density (stoichiometry of reaction: 1 mol ozone per mol degraded hydrocarbon) and 25% by electrophilic attack on the most polar bond or lowest atom-localisation energy. Pryor et al 12 observed that the ozonation of alkenes with electron-withdrawing substituents is mainly produced via 1, 3 dipolar cycloaddition. Moreover, alkenes in which the double bond is connected to electron-donating groups react many times faster than those in which it is connected to electron-withdrawing groups.…”
Section: Effect Of the Initial Concentration Of Ntsmentioning
confidence: 99%